Development of Batik Plotter and Dyeing Machine Based on Wireless Communication System - Winata, Bagas Aditya Putra; Taufik, Mochammad; Perdana, Ridho Hendra Yoga; Hidayati, Nurul (JURNAL JARTEL: Jurnal Jaringan Telekomunikasi, 2025)
The dyeing process in small-scale batik industries is generally performed by immersing fabric into a dye bath, which exposes operators’ hands to chemical dyes and may cause skin irritation. In addition, manual handling often leads to quality degradation, as dyes can penetrate unintended areas when the wax layer peels or cracks, particularly due to fabric folding, resulting in distorted batik patterns. To address these issues, this study proposes a Computer Numerical Control (CNC)-based automatic batik stamping machine to improve process consistency, efficiency, and operator safety. The developed system employs three stepper motors to control movement along the X-axis, Y-axis, and Z-axis, where the Z-axis regulates the motion of an electric canting stamp. Machine operation is controlled using Mach3 software, which generates G-code commands transmitted wirelessly to an Arduino microcontroller via Universal G-Code Sender. Experimental results show that the optimal operating temperature of the electric canting tool is within the range of 55–70°C, ensuring stable wax flow. Accuracy testing indicates an average positional deviation of approximately 0.7 mm across all axes, demonstrating good mechanical precision. Furthermore, the 433 MHz telemetry-based wireless communication system provides reliable control up to a distance of 50 meters.